Proposal for changes in competition system and wrestling rules for 2025 - Dokmanac, M. (International Journal of Wrestling Science, 2024)
At the Olympic Games in Paris, the wrestler (130 kg GR style - Chile) won the silver medal without scoring a single point. The judges awarded him 3 points for passivity and with 3 ground defenses he won a medal at the Olympic Games. This must be the reason to start making important rule changes when it comes to GR style. The biggest problem is the gifted passivity point. In my opinion, giving points for passivity in GR style must be removed. During the Olympic Games in Paris, I talked a lot with coaches from all over the world. On the basis of those conversations, I prepared the following proposals, which were supported by everyone.